ASODAT: una plataforma de información sobre el teatro clásico español a partir de bases de datos federadas - Ferrer Valls, Teresa; Fuertes Seder, Ariadna; Peña Ortiz, Raúl; García-Reidy, Alejandro; Josa Martínez, Dolores; Urzáiz Tortajada, Héctor (Talía. Revista de estudios teatrales, 2021)
In this article we present the first version of the online database ASODAT, a federation of four databases on different aspects of early modern Spanish theater and its performance. We explain the steps that we followed to create this federated system of databases, its objectives, and our preliminary results, as well as the perspectives of continuity and integration that this platform offers to researchers and new projects. In its current state, ASODAT provides information about plays and authors, manuscripts, censorship and songs related to theatrical texts.
Keywords: Spanish theater; Sixteenth and seventeenth centuries; Databases